EFEKTIVITAS STRATEGI PEMASARAN PRODUK TABUNGAN HAJI DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF DI BRI SYARIAH KANTOR CABANG PEMBANTU BOJONEGORO - Nur Azizah; Joko Hadi Purnomo; Niswatin Nurul Hidayati (MIYAH : Jurnal Studi Islam, 2020)
Abstract: This research aimed to explain how the marketing strategy of Pilgrimage savings products in increasing competitive advantage, how effective the marketing strategy of Pilgrimage savings products in increasing competitive advantage and what factors are hampering and supporting in marketing Pilgrimage savings products at BRI Syariah KCP Bojonegoro. This research was conducted at the BRI Syariah KCP Bojonegoro, located at Jalan Untung Suropati A No.9 Ruko Adipura Bojonegoro. The subjects used in this research to assess the effectiveness of Pilgrimage savings marketing are leaders, Branch Operation Superviors (BOS) and customer service, while the object is the marketing strategy, the effectiveness of marketing strategies, and inhibiting and supporting factors in marketing the Pilgrimage savings product. This research used data collection techniques through observation, interviews and documentation. The results of the research were marketing strategies which included (segmentation, marketing mix, conducting studies in mosques or mushallas, exploring customer profiles, and applying service strategies). The effectiveness of the marketing strategy of the Pilgrimage savings product is very effective in terms of its marketing strategy system through online media.Keywords: marketing strategy, and Pilgrimage saving